Risk assessments for chronic exposure of children and prospective parents to ethylbenzene (CAS No. 100-41-4). (14th September 2015) - Sweeney, Lisa M.; Kester, Janet E.; Kirman, Christopher R.; Gentry, P. Robinan; Banton, Marcy I.; Bus, James S.; Gargas, Michael L.
Abstract : Potential chronic health risks for children and prospective parents exposed to ethylbenzene were evaluated in response to the Voluntary Children's Chemical Evaluation Program. Ethylbenzene exposure was found to be predominately via inhalation with recent data demonstrating continuing decreases in releases and both outdoor and indoor concentrations over the past several decades. The proportion of ethylbenzene in ambient air that is attributable to the ethylbenzene/styrene chain of commerce appears to be relatively very small, less than 0.1% based on recent relative emission estimates. Toxicity reference values were derived from the available data, with physiologically based pharmacokinetic models and benchmark dose methods used to assess dose–response relationships. An inhalation non-cancer reference concentration or RfC of 0.3 parts per million (ppm) was derived based on ototoxicity. Similarly, an oral non-cancer reference dose or RfD of 0.5 mg/kg body weight/day was derived based on liver effects. For the cancer assessment, emphasis was placed upon mode of action information. Three of four rodent tumor types were determined not to be relevant to human health. A cancer reference value of 0.48 ppm was derived based on mouse lung tumors. The risk characterization for ethylbenzene indicated that even the most highly exposed children and prospective parents are not at risk for non-cancer or cancer effects of ethylbenzene.